2014
DOI: 10.1242/dev.105072
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient targeted mutagenesis in axolotl using Cas9 RNA-guided nuclease

Abstract: Among tetrapods, only urodele salamanders, such as the axolotl Ambystoma mexicanum, can completely regenerate limbs as adults. The mystery of why salamanders, but not other animals, possess this ability has for generations captivated scientists seeking to induce this phenomenon in other vertebrates. Although many recent advances in molecular biology have allowed limb regeneration and tissue repair in the axolotl to be investigated in increasing detail, the molecular toolkit for the study of this process has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 28 publications
3
54
1
Order By: Relevance
“…This difference in penetrance corresponded well to the intensity of lineage tracer fluorescence in the mutant embryos (Fig. 3), as reported in axolotl (Flowers et al, 2014). Going forward, sorting mutants according to lineage tracer intensity and distribution should allow researchers to separate and score complete versus partial mutant embryos.…”
Section: Discussionsupporting
confidence: 80%
“…This difference in penetrance corresponded well to the intensity of lineage tracer fluorescence in the mutant embryos (Fig. 3), as reported in axolotl (Flowers et al, 2014). Going forward, sorting mutants according to lineage tracer intensity and distribution should allow researchers to separate and score complete versus partial mutant embryos.…”
Section: Discussionsupporting
confidence: 80%
“…The latter study stands out in the scale and quality of effort, as the authors showed knock-out and precise mutation knock-in generation in the telomerase gene and a panel of aging-related genes thus positioning this species as an important model for aging research [88]. As we age, our ability to regenerate tissues decreases, so applying CRISPR/Cas9 in axolotl (Ambystoma mexicanum), a regenerative biology model system, may help solve regeneration puzzles with the first such study demonstrating mutant generation and optimizations aimed at achieving high levels of nearly completely null animals in the founder generation [89].…”
Section: Crispr/cas9 In Animal Modelsmentioning
confidence: 99%
“…However, gene targeting has limited applications in some organisms due to time-consuming procedures and the lack of available embryonic stem cells. Many recent studies have shown that CRISPRCas9 technology could be used for rapidly generating targeted genome modifications in the germ lines of various model organisms [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] , which will significantly advance the functional genomics. Microinjection of Cas9-encoding mRNA and customizable sgRNA into one-cell stage zebrafish embryos is able to efficiently modify the target genes in vivo in a simple, rapid and scalable manner 13,14 .…”
Section: Applications Of Crispr/cas9 Technology: Crispr-cas9 In the Gmentioning
confidence: 99%
“…CRISPR-Cas9 technology has been used for efficient genome engineering in many other model organisms, including Drosophila 19,20 , Caenorhabditis elegans 21 , Axolotl 22 , Xenopus tropicalis 23,24 , rat 25 and pig 26 . Significantly, the CRISPR-Cas9 system has been shown to be an efficient and reliable approach for targeted modification of cynomolgus monkey genomes 27 .…”
Section: Applications Of Crispr/cas9 Technology: Crispr-cas9 In the Gmentioning
confidence: 99%